THE RATES AND EXTENT OF TEXTURAL EQUILIBRATION IN HIGH-TEMPERATURE FLUID-BEARING SYSTEMS - Holness M.B.; Siklos S.T.C. (My University, 2000)
The geometry of fluid-filled pores in texturally equilibrated aggregates can, in theory, be uniquely determined given the porosity and the equilibrium dihedral angle for all possible orientations and combinations of the constituent solid phases. While it is useful to be able to do this, one should also ask whether, and to what extent, textural equilibrium is actually attained during fluid-present intervals in high-temperature rocks. In fact, textural equilibrium may be only rarely attained during melting of crustal rocks, and equilibration under mid-ocean ridges is possibly incomplete to depths as great as the garnet stability zone. There is very little published information on the rates of attainment of textural equilibrium in fluid-bearing geological environments. The available experimental data for the rates of growth of equilibrated domains are consistent with a power-law relationship between domain size and equilibration time with an exponent between 2 and 3. A simplified theoretical treatment of pore shape change governed by the Gibbs-Thompson relationship demonstrates that an exponent of 3 is to be expected for equilibration by diffusion within the fluid phase, with an effective diffusivity consistent with the available data.
Keywords: TEXTURAL EQUILIBRATION; FLUID-BEARING GEOLOGICAL SYSTEMS; HIGH-TEMPERATURE ROCKS